Global Power Dynamics in the Contemporary Space System - Francisco Del Canto Viterale (Systems)
In the 21st century, the space system has experienced a substantial shift from a simple unipolar to a new and more complex structure. This transition is the result of the emergence of new space powers and global power dynamics. The central hypothesis of this research work is that the space system is undergoing an intersystem transition from a unipolar, U.S.-dominant, post-Cold War space system to a new and more complex structure that includes new space powers and a redistribution and rebalancing of power dynamics. The unipolar structure that prevailed in the post-Cold War era has been replaced by a new space system, in which emerging space powers exhibit global ambitions and a willingness to compete with and challenge the United States’ dominance. These shifts in the number of space actors, power dynamics, and the structure of the space system necessitate novel scientific approaches. This research postulates the utilization of systems science as a means to enhance our comprehension of the intersystem transition and the rebalancing of power in the space system in recent decades. The result of this study is a comprehensive analysis of the major space actors in the 21st-century space system, the analysis of the redistribution of power among them, and the new power structure that has emerged.